Safety profile of remifentanil: A post-marketing study in Indonesia - Jarir At Thobari,, Jonathan Hasian Haposan, Lukman Ade Chandra,, Nastia Hidayati, Rianiasa Karunia Dewi, Rita Wahyu Purnamasari, Dyah Juliana Pudjiati (Journal of Applied Pharmaceutical Science, 2022)
Remifentanil is a novel short-acting μ-opioid receptor agonist. Hence, it can be used as an alternative to fentanyl with additional short-acting potential. However, the safety profile of remifentanil in the Indonesian population through post-marketing surveillance has not been evaluated yet. Therefore, this study aims to evaluate the safety profiles of remifentanil in a multicenter pharmacovigilance study in Indonesia. There were 42 patients who used remifentanil during the 3 months of observation in six referral hospitals in Indonesia. It was found that 35 patients (83%) experienced at least one adverse event. There were 54 adverse events recorded during the observations, with hypotension and bradycardia being the most common adverse events, followed by nausea, respiratory depression, dizziness, shivering, warm sensation, and muscle rigidity. Based on the previous safety data, most of these adverse events were recognized as common adverse drug reactions of remifentanil. The expert panel meeting concluded that, from those adverse events, 98% were possibly related to remifentanil and only one adverse event was unlikely related. Based on this pharmacovigilance study, there are no additional safety concerns related to remifentanil as an analgesic and sedative drug indicated for patients on intubation, invasive mechanical ventilation, and noninvasive ventilation.
Keywords: Remifentanil, postmarketing surveillance, pharmacovigilance, sedative